2012
DOI: 10.1097/coc.0b013e31821a9452
|View full text |Cite
|
Sign up to set email alerts
|

Combined High-dose Radiation Therapy and Systemic Chemotherapy Improves Survival in Patients With Newly Diagnosed Metastatic Nasopharyngeal Cancer

Abstract: High-dose RT is indicated for local disease control in patients with metastatic NPC, and may improve survival when actively used with systemic chemotherapy and local treatment for metastatic foci. Patients with single-organ metastases have a better prognosis as compared with those with more widespread metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 19 publications
9
62
1
1
Order By: Relevance
“…Since 2011, concurrent chemo/radiotherapy has been another choice for selected patients (patients with distant metastasis in limited site or with small tumor burden, or patients with symptoms in the primary or any nodal site) in the guideline, emphasizing the importance of multidisciplinary therapy in newly diagnosed metastatic NPC. Concurred closely with other studies (Cao et al, 2011;Lin et al, 2012), we found a combination of radiotherapy for nasopharynx improved the OS. But the prognosis did not significantly relate to different radiation doses and techniques.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Since 2011, concurrent chemo/radiotherapy has been another choice for selected patients (patients with distant metastasis in limited site or with small tumor burden, or patients with symptoms in the primary or any nodal site) in the guideline, emphasizing the importance of multidisciplinary therapy in newly diagnosed metastatic NPC. Concurred closely with other studies (Cao et al, 2011;Lin et al, 2012), we found a combination of radiotherapy for nasopharynx improved the OS. But the prognosis did not significantly relate to different radiation doses and techniques.…”
Section: Discussionmentioning
confidence: 59%
“…Our data indicated that early T-stage and N-stage, single organ with solitary metastasis were significant predictors for favorable survival, which concurred closely with other studies. In a study (Lin et al, 2012) of 170 NPC patients with lung metastasis alone, it was found that the disease-free internal was longer in patients with early T-stage (p=0.001) or N-stage (p=0.002). Another study suggested patients with metastasis to the lung and/or solitary lesions have a more favorable prognosis compared with those patients with multiple metastases located in other anatomic sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several retrospective studies demonstrated a survival benefit with the addition of locoregional definitive radiotherapy to systemic chemotherapy in patients with initially metastatic NPC [9][10][11]. However, in these studies, there were different combinations with respect to the timing of chemotherapy in relation to radiotherapy (i.e., induction, concurrent, adjuvant or other combination), which may have differential impact on treatment outcome.…”
Section: Introductionmentioning
confidence: 96%